Significance of Conserving Built Heritage on Commercial Property : A Case Study Of Little India, Kuala Lumpur - Thirunavukkrasu, Prasad (Research in Management of Technology and Business, 2021)
The conservation of built heritage in the capital city is a herculean task due to the rise of new development projects that is significant over the years. The main problems that threaten the initiative of conserving built heritage are urbanisation process that happened surrrounding the Little India. There were two objectives outline in this study namely, to identify the issues related to built heritage conservation and to study the benefits of conserving the built heritage of Little India for commercial property purposes. The respondents involved in this research are Kuala Lumpur City Hall (DBKL) officer and the communities of Little India, Kuala Lumpur comprises of shop owner and workers. Mix method approach are used where qualitative and quantitative method used to support the information obtained through interview and transaction price data. Based on the results, the researcher has found various issues arises namely the traffic congestion, limited parking spaces, lack of cooperation from building owners, lack of softscapes and blind walkway issues. From this investigation, Plaza Sentral and Boulevard has experienced increment in the commercial property value after the commencement of Little India project.